As Monita Secreta: História de um Best-seller AntijesuíticoThe Monita Secreta: The History of an anti-jesuitic bestseller (PerCursos, 2007)
História das origens e do percurso editorial de uma obra clássica de conspiracionismo que foi determinante para a afirmação da crença antijesuítica na Europa Moderna, onde Portugal e o Brasil tiveram um papel significativo. Análise dos conteúdos, significados e objetivos prosseguidos pelas ideologias que durante séculos têm continuado a propagandear esta contrafacção. Palavras-chave: Jesuítas; Mito; Conspiração; Desconstrução. Abstract: History of the origins and the editorial path of a classic conspirationism masterpiece that was crucial to the establishment of the anti-Jesuitic belief in Modern Europe, in which Portugal and Brazil played a significant role. Analysis of contents, meanings, and objectives pursued by the ideologies that, for centuries, have continued to advertize this counterfaction.Key Word: Jesuits; Myth; Conspiracy; Deconstruction.